KAJIAN ANALISIS HARGA SATUAN PEKERJAAN (AHSP) SNI 2016 DIBANDINGKAN DENGAN BINA MARGA 2020 PADA PEKERJAAN LAPIS ASPAL AC-BC DAN AC-WC - Riwibowo, Nola; Wijaya, Oky Dedy; Rohman, Miftahur; Afan, Moh. Midchol (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2023)
This research is a type of quantitative research with a case study approach, namely calculating the analysis of the unit price of road works carried out using the SNI 2016 and Bina Marga 2020 analysis methods. The locations used in this research are Jalan Dewi Sartika and Jalan Mojoranu Mastrip, Bojonegoro Regency. Based on the research results, it is known that there is a difference in the unit price of the work between the 2016 SNI analysis and the 2020 Bina Marga. In the Asphalt Concrete-Binder Course (AC-BC) work using the Bina Marga 2020 method, the difference in work unit prices is greater than the 2016 SNI analysis of 1.09% for Jalan Dewi Sartika and 4.38% for Jalan Mojoranu Mastrip. Whereas the Asphalt Concrete-Wearing Course (AC-WC) work using the Bina Marga 2020 method also has a larger difference in the unit price of work compared to the 2016 SNI analysis of 47.54% for Jalan Dewi Sartika and 51.77% for Jalan Mojoranu Mastrip. The ratio of unit price comparisons between the 2016 SNI analysis and 2020 Bina Marga for the Asphalt Concrete-Binder Course (AC-BC) work using the Bina Marga 2020 method has a larger ratio difference compared to the 2016 SNI analysis of 1.01 for Jalan Dewi Sartika and 1.04 for Jalan Mojoranu Mastrip. Meanwhile, the Asphalt Concrete-Wearing Course (AC-WC) work using the Bina Marga 2020 method also has a larger ratio difference compared to the 2016 SNI analysis of 1.48 for Jalan Dewi Sartika and 1.52 for Jalan Mojoranu Mastrip. All supporting components in the Asphalt Concrete-Binder Course (AC-BC) and Asphalt Concrete-Wearing Course (AC-WC) have different differences in work unit prices and ratios. Based on these differences it is known that the most efficient components are workers and foremen.